2011
DOI: 10.1007/s12024-011-9257-2
|View full text |Cite
|
Sign up to set email alerts
|

Upper and lower gastrointestinal endoscopy mortality: the medical examiner’s perspective

Abstract: Fiberoptic endoscopy is utilized to diagnose and treat a wide variety of gastrointestinal tract diseases and is currently one of the most commonly performed invasive medical procedures. Though generally considered to be safe, the procedure may be associated with serious complications including death. Herein, we correlate the clinical history with the autopsy findings in gastrointestinal endoscopy (GIE) related fatalities that were reported to the New York City Medical Examiner Office over a 5 year period. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 31 publications
(49 reference statements)
1
3
0
Order By: Relevance
“…In a recent study, the death rate as a result of bleeding or perforation was estimated to be 0.013% in a Swedish cohort study of 593,315 colonoscopies from 2001 to 2013. 2 This is consistent with another study by deRoux and Sgarlato, which showed the colonoscopy death rate in a small population in New York City to be 0.014% between 2005 and 2009 3 . In Sweden, there are few studies concerning colonoscopy‐related AEs.…”
Section: Introductionsupporting
confidence: 85%
See 1 more Smart Citation
“…In a recent study, the death rate as a result of bleeding or perforation was estimated to be 0.013% in a Swedish cohort study of 593,315 colonoscopies from 2001 to 2013. 2 This is consistent with another study by deRoux and Sgarlato, which showed the colonoscopy death rate in a small population in New York City to be 0.014% between 2005 and 2009 3 . In Sweden, there are few studies concerning colonoscopy‐related AEs.…”
Section: Introductionsupporting
confidence: 85%
“…2 This is consistent with another study by deRoux and Sgarlato, which showed the colonoscopy death rate in a small population in New York City to be 0.014% between 2005 and 2009. 3 In Sweden, there are few studies concerning colonoscopy-related AEs. 2,4,5…”
Section: Introductionmentioning
confidence: 99%
“…This approach is based on the observation that some miRNAs can also downregulate mRNA levels in addition to down regulating protein levels of their target genes [136]. An experimental validation of miRNA target sites has been to express a miRNA in vivo while simultaneously expressing and monitoring the target mRNA linked to a reporter gene, i.e., Luciferase [134,[137][138][139][140][141][142][143][144].…”
Section: Discussionmentioning
confidence: 99%
“…An additional approach towards data integration aimed at the identification of conserved changes to reduce background noise in expression profiling studies, and subsequently in miRNA studies, is represented by cross-species comparison of tumors from human patients and animal models of cancer [143]. This approach is expected to pinpoint genes of conserved functional relevance in the process of tumor formation and progression in mammalian intestinal tumorigenesis.…”
Section: Recommendationsmentioning
confidence: 99%